1998
DOI: 10.1021/ef9702052
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of H2S Reaction with Calcined Calcium-Based Sorbents

Abstract: Sulfidation experiments at atmospheric pressure in a thermogravimetric analyzer were performed with two calcined limestones and a fully calcined dolomite at temperatures between 450 and 700 °C and with sorbent particle sizes between 0.4 and 1.6 mm. The effects of reaction temperature, sorbent particle size, and H2S concentration were analyzed. The sulfidation rate of the dolomite and a limestone increased with temperature in all of the ranges tested. However, the sulfidation rate of the other limestone increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…As a result, an increase in the mass of the sample was registered [59]. In addition, an effective oxygen transport capacity, R OC,eff , is defined considering that some sulphur is released to gas phase as SO 2 , which decrease transferable oxygen.…”
Section: Results From Tga Experimentsmentioning
confidence: 99%
“…As a result, an increase in the mass of the sample was registered [59]. In addition, an effective oxygen transport capacity, R OC,eff , is defined considering that some sulphur is released to gas phase as SO 2 , which decrease transferable oxygen.…”
Section: Results From Tga Experimentsmentioning
confidence: 99%
“…They found that all particle size of 125–180 μm was limited by diffusion through CaSO 4 layer in the temperature range of 750–900°C and the activation energies of effective diffusivity through the CaSO 4 layer were 110–280 kJ/mol, whereas 1–5‐μm particles the sulphation was limited by chemical reaction kinetics above 850°C. Adαnez and co‐workers [49, 50] used the changing grain size model (CGSM) proposed by Georgakis et al [43] combined with the molecular scale hypotheses of Attar et al [51] to determine the kinetic parameter data for the sulfidation reaction over a broad range of particle sizes and temperatures. Good agreement between measured and predicted conversion time curves and sulfur distributions inside the particles was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur release and removal by Ca-based sorbent in fluidized bed during coal gasification and combustion has been reported by many researches [1][2][3][4] . In recent years, more investigations emphasized sulfur transfer and distribution during coal pyrolysis or gasification.…”
Section: Introductionmentioning
confidence: 99%